Pengaruh Variabilitas Laba Akuntansi, Variabilitas Persediaan, Financial Leverage dan Kepemilikan Manajerial Terhadap Pemilihan Metode Akuntansi Persediaan pada PT. Petro Abadi Niaga - Lianna Primavera; Thomas Sumarsan Goh; Elidawati Elidawati; Edison Sagala (Universitas Batanghari Jambi, 2022)
This study aims to analyze whether variables such as accounting profit, inventory, financial leverage and managerial ownership affect the selection of inventory accounting methods. The data analysis method used in this study is statistical analysis (logistical regression) which is carried out with various tests, namely classical assumption test, testing the entire model, coefficient of determination, assessing the feasibility of logistic regression and hypothesis testing. The results of this study indicate that the variability of accounting earnings partially has no significant effect on the selection of inventory accounting methods. Inventory variability partially has a significant effect on the selection of inventory accounting methods. Financial leverage partially has no significant effect on the selection of inventory accounting methods. Partial managerial ownership has no significant effect on the selection of inventory accounting methods. Accounting profit variability, inventory variability, financial leverage and managerial ownership have a significant and simultaneous effect on the selection of inventory accounting methods.